Penerapan UML dalam Rancang Bangun Sistem Informasi Pengolahan Data Penggajian Karyawan CV. XYZ - Forkas Tiroy Santos Butarbutar (INDO PUBLISHING, 2026)
The purpose of this research is to develop a good information system in presenting information according to the company's needs. At the time of this research, the company experienced difficulties in processing its employee data, resulting in errors in determining employee salaries. For the purposes of developing this employee data processing information system, the waterfall method was used, which is believed to be quite relevant to support system development. And for the design of the information system needed in this research, the UML design was applied to ensure the system flow runs according to the system development objectives. The results of this research are displaying the system interface, namely: attendance data transactions, overtime transactions, payroll data and from this information system produces printed products of attendance reports, printed overtime reports, printed payroll reports and printed pay slips. Thus, it is hoped that through this research, the company can properly maximize the use of the information system that has been created to help the company's operations be run more efficiently.